WAYS TO IMPROVE THE SYSTEM OF SOCIAL AND PSYCHOLOGICAL MECHANISMS OF MANAGEMENT ACTIVITIES - Cherusheva, Galyna (SWorld-Ger Conference proceedings, 2025)
It is well known that any improvements in an organization’s activities cannot take place without the personal and professional growth of each employee, their awareness, and the development of their competence. The personal value of each employee of the or